When Organ Donation from Living Donors Serves as the Main Source of Organ Procurement: A Critical Examination of the Ethical and Legal Challenges to Turkey's Recent Efforts to Overcome Organ Shortage - GÖRKEY, ŞEFİK (ELSEVIER SCIENCE INC, 2013)
Despite the fact that Turkey has implemented a number of legislative and regulatory efforts to increase cadaveric donations, live donors still serve as the main source of organ procurement in this country. To address this problem, Turkey's regulatory authorities have sought to increase the number of brain death declarations. A new regulation issued in 2012 repeats the criteria for brain death that were first issued in 1993. This paper argues that these efforts are far from adequate owing to a number of complicated, ethical, and legal challenges that must be addressed to increase cadaveric organ donations. After examining these factors, which are completely neglected in current policies, we conclude that Turkey needs a realistic ethically justifiable organ procurement policy that must be supported by a framework of patient rights to implement the concept of patient autonomy and respect for human dignity in health care services as the primary goal.
Keywords: ATTITUDES; KNOWLEDGE